Women in the Midst of Violence From a Human Rights Perspective - Astuti Nur Fadillah; Patrick Corputty (Fakultas Hukum Universitas Pattimura, 2022)
Introduction: Many people think that women are weak and do not have the power to fight and defend their rights. In accordance with the constitutional mandate, every citizen has the right to feel safe and free from all forms of violence.Purposes of the Research: This study aims to find out about women in the midst of a vortex of violence from a human rights perspective.Methods of the Research: The research method used is normative juridical research that uses legal sources of material obtained through literature studies and statutory regulations.Results of the Research: Violence against women is seen as part of the violation of human rights. The law on human rights in Indonesia is very strict about women's rights. Women have many contributions to the welfare of society so women must be treated by protecting their rights as a woman.